1979
DOI: 10.1111/j.1432-1033.1979.tb12992.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Isoenzymes of Pig‐Liver Esterase 2. Kinetic Studies

Abstract: The kinetic properties of two of the partially separated isoenzymes I and V of pig liver esterase were studied. The cholinesterase-like isoenzyme I hydrolyses butyrylcholine as well as various other esters and aromatic amides. This isoenzyme is sensitive to 0.01 mM physostigmine and to fluoride. The second type (isoenzyme V) has the features of the so-called aliesterase: it acts preferentially on short-chain aliphatic esters, does not hydrolyse butyrylcholine and has only low activity towards amides. Further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 23 publications
4
63
0
3
Order By: Relevance
“…The product inhibition patterns agree with the Uni-Bi kinetic scheme, with alcohol as the leading product (Hofstee, 1972). Activation observed at low concentrations of p-nitrophenol may be due to the direct reaction of the nucleophilic alcohol with acyl-enzyme intermediate (Junge and Heymann, 1979;Farb and Jencks, 1980) to generate the corresponding aliphatic ester and results in the release of the free enzyme as reported for other esterases.…”
Section: Discussionsupporting
confidence: 70%
“…The product inhibition patterns agree with the Uni-Bi kinetic scheme, with alcohol as the leading product (Hofstee, 1972). Activation observed at low concentrations of p-nitrophenol may be due to the direct reaction of the nucleophilic alcohol with acyl-enzyme intermediate (Junge and Heymann, 1979;Farb and Jencks, 1980) to generate the corresponding aliphatic ester and results in the release of the free enzyme as reported for other esterases.…”
Section: Discussionsupporting
confidence: 70%
“…In vitro hydrolysis studies of esters have been performed with specific carboxylesterase isoenzymes isolated from pig and rat livers (Junge & Heymann, 1979;Arndt & Krisch, 1973). The isoenzyme I exhibits an increase in enzyme binding (lower Km) and maximum velocity (Vmax) as the carbon chain length of either the alcohol or carboxylic acid component of the substrate increases.…”
Section: Iii4 Ester Hydrolysismentioning
confidence: 99%
“…9 Time history of characteristic atom-atom distances in the active site of the PLE1 monomer during the molecular dynamics run. The black line indicates high stability of the SER204-HIS449 hydrogen bond.…”
Section: Figure Captionsmentioning
confidence: 99%
“…A further isoenzyme which complements the mutation pattern of PLE3 and PLE5 was described as alternative PLE (APLE) [14]. Determination of the molecular weight has shown that under physiological conditions the enzyme mostly forms trimers which contain a random combination of different isoenzyme monomers [8,9]. 3 In this paper we focus on 3D models for the enzyme structure without deformation by an embedded substrate as a first step towards understanding the reaction mechanism of the enzyme and its enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation